Sediment Organic Carbon Stock at the Muara Gembong Mangrove Area of Bekasi, West Jawa - Muazzasari, Fitra; Japa, Lalu; Suyantri, Eni (Jurnal Biologi Tropis, 2025)
Mangrove ecosystems have a crucial role in absorbing and storing carbon, which contributes to controlling greenhouse gas emissions, especially carbon dioxide (CO₂) as the largest contributor to greenhouse gases. This research aims to measure sediment organic carbon stocks (SOCS) in the Muara Gembong mangrove area, Bekasi, West Java. Sediment samples were taken by purposive sampling from three locations with different mangrove characteristics, namely Station 1, Station 2 and Station 3. Samples were analyzed using the Loss on Ignition (LOI) method to determine the organic carbon content in the sediment. The research results showed that the highest carbon stock 669.95 tonnes/ha was found at Station 1, while the lowest carbon stock 2 501.78 tonnes/ha was at Station. In general, organic carbon content increases in deeper sediment layers. The dominant sediment texture is silty and silty loam, which supports carbon storage capacity. This research highlights the importance of preserving mangrove ecosystems as an effort to mitigate climate change through optimizing carbon storage in mangrove sediments.